Anthropometric measurements of the arm span and their correlation with the stature of Bangladeshi adult muslim females - Laila, SZ; Begum, JA; Ferdousi, R; Parveen, S; Husain, MS; Holy, SZ; Islam, MS (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):561-4 The abstract of this article is available on the PubMed website